2011
DOI: 10.1002/asia.201100645
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Thermal Expansion of Clathrate Hydrates Induced by Asymmetric Guest Molecules

Abstract: We investigated for the first time the abnormal thermal expansion induced by an asymmetric guest structure using high-resolution neutron powder diffraction. Three dihydrogen molecules (H(2), D(2), and HD) were tested to explore the guest dynamics and thermal behavior of hydrogen-doped clathrate hydrates. We confirmed the restricted spatial distribution and doughnut-like motion of the HD guest in the center of anisotropic sII-S (sII-S=small cages of structure II hydrates). However, we failed to observe a mass-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Considering the RDFs in Figure , dispersed molecular motion and thermal expansion of a large guest make the butyraldehyde closer to the host cage, and this can lead to a larger attractive or repulsive force. This supposition corresponds to a previous study that the molecular motion of the guest molecule in the hydrate cage affects the thermal expansivity . Also, Tse et al reported that the guest–host interaction enhances the anharmonic terms of the hydrate crystal potential and causes larger thermal expansivity .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Considering the RDFs in Figure , dispersed molecular motion and thermal expansion of a large guest make the butyraldehyde closer to the host cage, and this can lead to a larger attractive or repulsive force. This supposition corresponds to a previous study that the molecular motion of the guest molecule in the hydrate cage affects the thermal expansivity . Also, Tse et al reported that the guest–host interaction enhances the anharmonic terms of the hydrate crystal potential and causes larger thermal expansivity .…”
Section: Resultssupporting
confidence: 89%
“…This supposition corresponds to a previous study that the molecular motion of the guest molecule in the hydrate cage affects the thermal expansivity. 56 Also, Tse et al reported that the guest−host interaction enhances the anharmonic terms of the hydrate crystal potential and causes larger thermal expansivity. 57 Accordingly, through the simulation results in Figures 7 and 8, it can be speculated that the molecular thermal expansivity and motions varied with the structure of the large guest molecules, resulting in differences in guest−host interactions, hydrate crystal potential, and thermal expansivity of the lattice.…”
Section: The Journal Of Physical Chemistry Cmentioning
confidence: 99%
“…Both molecular mass and motion of guest molecules in the hydrate cavities could determine the cavity size and the corresponding structure of hydrates. However, the molecular size of a hydrate former has been recognized as a key factor in determining the structure of clathrate hydrates. ,, A molecular size above 7.5 Å is too large to be captured into the small cages of structure II (sII) hydrate. , The molecular size of pyridine and pyrrole was determined through the calculation of optimum molecular structures by using Gaussian 03 . The B3LYP method with the 6-311 ++ G (d,p) basis set was used for this calculation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the molecular size of a hydrate former has been recognized as a key factor in determining the structure of clathrate hydrates. 1,21,22 A molecular size above 7.5 Å is too large to be captured into the small cages of structure II (sII) hydrate. 1,23−25 The molecular size of pyridine and pyrrole was determined through the calculation of optimum molecular structures by using Gaussian 03.…”
Section: ■ Results and Discussionmentioning
confidence: 99%